Comparison of Translation Quality between Large Language Models and Neural Machine Translation Systems: A Case Study of Chinese-English Language Pair - Li, Xinchen (International Journal of Education and Humanities, 2024)
A number of Neural Machine Translation (NMT) systems have already demonstrated their strength to undertake various translation tasks which are not too demanding. However, the incredible advancement of AI technology in recent years has endowed Large Language Models (LLMs) with great potential, so we may imagine that they may even do better than NMT working as translators. To figure out whether LLMs have better performance than NMT in translation, and how genres and translation directions may influence translation quality, this article chose two LLMs, namely, ChatGPT 3.5 and Wenxin Yiyan, or ERNIE Bot 3.5, and one NMT system, namely, DeepL, to test and compare their performance in Chinese-English translation, employing a quantitative method including BLEU scoring and SPSS analysis. The results show that there is no significant improvement in these LLMs’ translation quality compared with the NMT system, and all the chosen systems tend to perform better in non-literary translation than in literary translation and produce TTs of higher quality in Chinese-English translation than in English-Chinese translation